Narrativas da Bôta nos Contos de Walcyr Monteiro (Revista Internacional de Folkcomunicação, 2025)
The objective of this study is to analyze how the representation of riverside women in the Amazon region of Pará is presented in two narratives of the bôta (sic) within the sociocultural context of the riverside people's imagination. This interdisciplinary exploratory study with a qualitative approach analyzes two popular stories published by Walcyr Monteiro, in Visagens, Assombrações e Encantamentos da Amazônia (Nos. 03 and 05), published in 2000, about the female boto, called bôta in the analyzed tales, an enchanted being that is part of the cycle of life and the tides, intertwining the individual and collective imagination with affections and lifestyle. The article was based, among others, on the social cement of Maffesoli (2010), the sociocultural context of the imagination of Laplantine and Trindade (1997), and within the structures of Barthes' narratives (1975). The representation of riverside women in the bôta tales reveals a rich culture with profound influences on the Melgaço community.